2010
DOI: 10.1007/s10709-010-9511-7
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of quantitative trait loci controlling barley flour pasting properties

Abstract: Pasting properties are important characteristics of barley starch from a processing standpoint. A shorter time to peak viscosity and lower pasting temperature are favorable to both malting and food processing. This study was conducted to identify quantitative trait loci (QTLs) determining pasting properties of barley flour using a doubled haploid population of 177 lines from the cross between six-rowed Yerong and two-rowed Franklin. Yerong is a feed barley with a longer time to peak viscosity and a higher past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…For example, most QTL for rice starch quality co-localise with waxy (wx) and alkali degeneration (alk) genes (Bao et al 2003;Tian et al 2005). Wang et al (2010) identified 21 QTL associated with barley flour pasting properties and showed the potential of the markers for use in marker-assisted selection (MAS). It was found that SSIIa of maize affected starch structure and its resultant physiochemical properties, which is useful for a variety of applications that require freeze-thaw stability (Zhang et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For example, most QTL for rice starch quality co-localise with waxy (wx) and alkali degeneration (alk) genes (Bao et al 2003;Tian et al 2005). Wang et al (2010) identified 21 QTL associated with barley flour pasting properties and showed the potential of the markers for use in marker-assisted selection (MAS). It was found that SSIIa of maize affected starch structure and its resultant physiochemical properties, which is useful for a variety of applications that require freeze-thaw stability (Zhang et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Flour pasting properties are important quality traits and have close relationship with malting quality [ 83 , 64 ] and food processing quality [ 65 ]. Pasting properties have been found to be influenced by genotype [ 83 , 84 ] and environment [ 65 , 84 86 ]. Earliness per se can also influence grain protein content [ 49 ] thus pasting properties [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Earliness per se can also influence grain protein content [ 49 ] thus pasting properties [ 87 ]. Several QTL have been identified for pasting properties in barley [ 86 ]. These QTL for pasting properties are located on chromosomes 1H, 2H, 3H, 4H, 6H and 7H [ 86 ] with no QTL on 5H, indicating that may be unlikely that this chromosome segment would affect pasting properties.…”
Section: Discussionmentioning
confidence: 99%
“…High N treatment showed significant reduction in phytase activity, which may be related to the higher average protein content (86.8 mg·g −1 ) caused by the higher rate of N application compared to the average protein content of 77.4 mg·g −1 where a low rate of N was applied. Samples from FVRS showed the highest phytase activity, which may be due to the low protein content of the grains [41]. The low phosphorus content in Forthside soil which has very high P fixing capacity could also cause an elevated phytase activity as phytase is used to maintain adequate available P for growth of the plants with P deficient [42].…”
Section: Discussionmentioning
confidence: 99%